Flowsheet Options for Cobalt Recovery in African Copper–cobalt Hydrometallurgy Circuits. (4th May 2019) - Sole, Kathryn C.; Parker, John; Cole, Peter M.; Mooiman, Michael B.
ABSTRACT: The price of cobalt has increased by some 450% in the past two years, mainly due to increasing demand for lithium–ion batteries. With an official 2017 production of 64 kt, the Democratic Republic of Congo produces more than half of the world's cobalt. African Copperbelt operations have traditionally focused on copper production; however, it has now become imperative to also consider cobalt recovery from these ores. A plethora of processing routes is possible. Most hydrometallurgical flowsheets recover cobalt from the raffinate of the low-grade copper solvent-extraction circuit. Downstream purification processes include sequential precipitation with a variety of reagents, solvent extraction, and ion exchange. Product choices include hydroxide, carbonate, sulfate, and metal cathode. This study assesses technical and economic advantages and limitations of various approaches to the hydrometallurgical processing of cobalt in an African context.